The Effect of a Training Program Based on the Bar-on Model for Emotional Intelligence to Improve Body Image in Jordan - Al-Shamaileh, Nisreen (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to investigate the effectiveness of an emotional intelligence-based training program on improving body image among a sample of adolescent girls aged between 12 and 15 years. Methods: The study sample consisted of 28 adolescent girls who scored the lowest on the body image scale, randomly assigned to an experimental group and a control group. To achieve the study objectives, a training program consisting of 21 sessions was developed based on the dimensions of the Bar-On model: Personal dimension, Interpersonal dimension, Adaptability, Stress Management, and General Mood. Results: The Mann-Whitney U test and Wilcoxon signed-rank test revealed the effectiveness of the training program in improving body image among adolescent girls at a significance level of (α≤0.05) in favor of the experimental group. The results also showed improvements in the dimensions of overall appearance, weight, face, and body areas for the experimental group in the post-test, but no significant changes were observed in the attitude towards cosmetic procedures. This might be attributed to the models presented to adolescents through media, modern communication, and intensive promotion of cosmetic procedures via these platforms. Conclusions: Based on the results, it is evident that the emotional intelligence program was effective in improving body image among adolescent girls.